2021
DOI: 10.1071/py20307
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning in dementia: a qualitative study of Australian general practitioners

Abstract: As the population ages, so does the prevalence of dementia, a condition in which timely advance care planning (ACP) is recommended. This study explored the barriers and enablers of ACP for Australian GPs caring for people with dementia. Semi-structured qualitative telephone interviews informed by the theoretical domains framework (TDF) were conducted with 16 GPs from the south-east region of metropolitan Melbourne. The most prevalent domains of the TDF were: (1) environmental context and resources; (2) beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In general, dementia leaves people with a relatively long timeframe of loss of ability to self-manage care and diminishing cognitive function ( Gaster et al, 2017 ). Despite ongoing discussions about the value of ACP ( Tishelman et al, 2021 ), it is argued that ACP can be particularly relevant for people with dementia and their caregivers as the condition eventually precludes patients from taking part in their own treatment decisions ( Alam et al, 2022 ). In case of Alzheimer’s Disease, diagnosis can be made during stages of mild cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, dementia leaves people with a relatively long timeframe of loss of ability to self-manage care and diminishing cognitive function ( Gaster et al, 2017 ). Despite ongoing discussions about the value of ACP ( Tishelman et al, 2021 ), it is argued that ACP can be particularly relevant for people with dementia and their caregivers as the condition eventually precludes patients from taking part in their own treatment decisions ( Alam et al, 2022 ). In case of Alzheimer’s Disease, diagnosis can be made during stages of mild cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Fearing a shift in patients’ preferences as the condition progresses was also identified as causing reluctance for physicians to make advance decisions with people with dementia ( De Vleminck et al, 2014 ). Conversely, a qualitative study also found that beliefs about the perceived benefits of ACP can motivate physicians to engage people with dementia in the process, such as the belief that ACP would align patients’, family caregivers’ and clinicians’ care goals ( Alam et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation